Analysis of Employee Job Satisfaction Based on the Influence of Leadership and Organizational Culture on the Millennial Generation in South Jakarta - Anan Dul Manan; Muhammad Yusuf (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine the effect of Leadership and Organizational Culture on Job Satisfaction of Millennial Generation Employees in South Jakarta. This research method uses associative research which aims to determine the effect between dependent variables on independent variables. The population in this study is unknown because of the very large number, This study uses the Cochran determination formula and gets the results of 97 respondents, with the random sampling method, or the technique of selecting a group of subjects randomly or based on certain characteristics that are considered as characteristics of the population that have been identified. Based on the results of the analysis, Leadership has a positive and significant effect on Job Satisfaction, this is shown in the Tcount> TTable (3.336> 1.985) and is significant at 0.01 <0.05 or 5%, so Ho is rejected and Ha is accepted. Other outcome variables also state that Organizational Culture has a positive and significant effect on Job Satisfaction, this is shown in the Tcount> TTable (8.089> 1.985) and is significant at 0.000 <0.05 or 5%, so Ho is rejected and Ha is accepted. Based on the results of the study, it shows that Leadership and Organizational Culture simultaneously have a positive and significant effect on Job Satisfaction of Millennial Generation Employees in South Jakarta. This is evidenced by the F test value that the Fcount value is 280.568 where the Fcount value> FTable is 280.568> 3.09 and also a significant value <0.05 or 0.000 <0.05